Incidence and prevalence of coma in the UK and the USA. Issue 5 (1st September 2022) - Kondziella, Daniel; Amiri, Moshgan; Othman, Marwan H; Beghi, Ettore; Bodien, Yelena G; Citerio, Giuseppe; Giacino, Joseph T; Mayer, Stephan A; Lawson, Thomas N; Menon, David K; Rass, Verena; Sharshar, Tarek; et al.
Abstract: The epidemiology of coma is unknown because case ascertainment with traditional methods is difficult. Here, we used crowdsourcing methodology to estimate the incidence and prevalence of coma in the UK and the USA. We recruited UK and US laypeople (aged ≥18 years) who were nationally representative (i.e. matched for age, gender and ethnicity according to census data) of the UK and the USA, respectively, utilizing a crowdsourcing platform. We provided a description of coma and asked survey participants if they—'right now' or 'within the last year'—had a family member in coma. These participants (UK n  = 994, USA n  = 977) provided data on 30 387 family members (UK n  = 14 124, USA n  = 16 263). We found more coma cases in the USA ( n  = 47) than in the UK ( n  = 20; P  = 0.009). We identified one coma case in the UK (0.007%, 95% confidence interval 0.00–0.04%) on the day of the survey and 19 new coma cases (0.13%, 95% confidence interval 0.08–0.21%) within the preceding year, resulting in an annual incidence of 135/100 000 (95% confidence interval 81–210) and a point prevalence of 7 cases per 100 000 population (95% confidence interval 0.18–39.44) in the UK. We identified five cases in the USA (0.031%, 95% confidence interval 0.01–0.07%) on the day of the survey and 42 new cases (0.26%, 95% confidence interval 0.19–0.35%) within the preceding year, resulting in an annual incidence of 258/100 000 (95% confidence interval 186–349) and a point prevalence of 31 cases per 100 000 population (95% confidence interval 9.98–71.73) in the USA. The five most common causes were stroke, medically induced coma, COVID-19, traumatic brain injury and cardiac arrest. To summarize, for the first time, we report incidence and prevalence estimates for coma across diagnosis types and settings in the UK and the USA using crowdsourcing methods. Coma may be more prevalent in the USA than in the UK, which requires further investigation. These data are urgently needed to expand the public health perspective on coma and disorders of consciousness. Abstract : The epidemiology of coma is unknown because case ascertainment with traditional methods is difficult. Crowdsourcing observations from 30 387 family members, Kondziella et al. of the Curing Coma Campaign provide the first data on coma incidence and prevalence in the UK and the USA (pooled annual incidence, 201 coma cases/100 000 population). Graphical Abstract: Graphical abstract Video Abstract: